Il fallimento di una vita inabituale: Henry James e la costruzione della «nostra eroina» Isabel Archer (Itinera, 2024)
This article aims to raise crucial aspects of the philosophy of habit found in late 19th-century literature, particularly through an examination of Henry James’ portrayal of his character Isabel Archer. This goal is pursued through the analysis of two interconnected aspects forming the theoretical core of this contribution. Firstly, the focus is on Isabel Archer’s psychological depiction as a fundamental contribution of the English and American literature on the theme of habit, especially during the latter half of the 19th century. By contextualizing James’ work, exploring links to Peirce’s pragmatist philosophy and habit theory, the centrality of habit reflection in the psychological structuring of characters, interwoven with philosophical and narrative theories of individuality, is revealed. Furthermore, this reflection provides interpretative keys to understanding Henry James’ narrative choices concerning Isabel’s fate in the novel. Then this article directly specifically examines the construction of Isabel’s self which unfolds through the entire narrative events. The interpretative hypothesis guiding the investigation focuses on the connection between Isabel’s attempts to conduct life without habit and the resulting errors in judgment. To support this hypothesis, the importance of comparing key characters such as Gilbert Osmond and Madame Merle is highlighted. Through the narrative, it will emerge a peculiar ontological structure of the concept of habit. Moreover, through the psychological portraits in the novel, a critical exploration of James’ idea of individuality arises — acknowledging social dynamics and the ontological force of habit, rejecting the dichotomy represented by an optimistic individualism and a degenerate conventional life. The conclusion asserts that Isabel’s pursuit of an unhabitual life inevitably leads to failure. The solution does not lie in a rigid, conventional, dichotomous view of habit. Instead, James argues for a dynamic, relational view of habit: a fundamental aspect of being that must be acknowledged to understand the mechanisms that lead us from the variety of possibilities to the limited “actualities” of life. Through these two interrelated perspectives, the article aims to illuminate the psychological depth of Isabel Archer’s character, demonstrating how her story represents a cornerstone in the broader discussion of the nature and evolution of habit in 19th- century literature. From that, it sets the stage for a more comprehensive discussion on habit’s role in shaping characters and narratives during this historical period.
Keywords: Habit, English novel, Henry James, Self, Pragmatism